2016
DOI: 10.1038/srep36413
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to extremely low frequency electromagnetic fields alters the behaviour, physiology and stress protein levels of desert locusts

Abstract: Electromagnetic fields (EMFs) are present throughout the modern world and are derived from many man-made sources including overhead transmission lines. The risks of extremely-low frequency (ELF) electromagnetic fields are particularly poorly understood especially at high field strengths as they are rarely encountered at ground level. Flying insects, however, can approach close to high field strength transmission lines prompting the question as to how these high levels of exposure affect behaviour and physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 56 publications
(60 reference statements)
1
36
0
Order By: Relevance
“…At ground level ELF EMFs generated under 400 kV transmission lines can reach magnetic flux densities of 100 µT 10 but flying insects could be exposed to even higher levels closer to the conductor, for example 0.6 mT at 1 m, and 14 mT at 1 cm 16 . Recent studies on the desert locust highlight the potential impact of ELF EMFs on insects, where high levels lead to physiological and behavioural changes as well as increased levels of stress proteins 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At ground level ELF EMFs generated under 400 kV transmission lines can reach magnetic flux densities of 100 µT 10 but flying insects could be exposed to even higher levels closer to the conductor, for example 0.6 mT at 1 m, and 14 mT at 1 cm 16 . Recent studies on the desert locust highlight the potential impact of ELF EMFs on insects, where high levels lead to physiological and behavioural changes as well as increased levels of stress proteins 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the area around power lines where pollinators may be affected by acute EMF exposure may, therefore, be high. Given what we already know of the effects of EMFs on insects 17 the opportunity is within our grasp to determine the impact of acute ELF EMFs on important pollinators. Here we focus on the commercially important honey bee and ask how ELF EMFs, at strengths found in the environment, affect their motor, cognitive and feeding abilities.…”
Section: Introductionmentioning
confidence: 99%
“…There are also reports showing that EMF affects heat shock protein (HSP) accumulation in cells (Tokalov and Gutzeit 2004 ; Alfieri et al 2006 ; Bernardini et al 2007 ; Li et al 2013 ; Wyszkowska et al 2016 ). Thus, the increase in latency to escape from heat in the examined cockroaches may be a result of heat shock proteins accumulation, which act as molecular chaperones and help denaturated proteins to refold.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of EMF exposure on insect morphology, physiology and behavior have been proved previously. The EMF exposure induced changes in: mosquito egg hatching (Pan and Liu 2004 ), ovipositon in Drosophila (Gonet et al 2009 ), locomotor activity of desert locust and American cockroach (Wyszkowska et al 2006 , 2016 ) or antioxidant defense in Baculum extradentatum (Todorović et al 2012 ). EMF exposure has been also shown to induce a release of octopamine—an insect ‘stress hormone’ in American cockroach (Wyszkowska et al 2006 ), whereas the static electric field exposure elevated octopamine levels in Drosophila brain (Newland et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that ELF and EMF cause some physiological and behavioral changes on insects and increase stress protein levels. (Wyszkowska et al2006; Wyszkowska et al 2016). In another study carried out by Rooder (1999), they found that there was a significant increase in the motor activity of insects as EMF increased octopamine levels in insects.…”
Section: Introductionmentioning
confidence: 99%